Transition and coherence in intellectual property law essays in honour of Annette Kur - Bruun, Niklas 1950-; Dinwoodie, Graeme B. 1966-; Levin, Marianne 1942-; Ohly, Ansgar 1965- (Cambridge University Press, 2021)
"As its economic potential has rapidly expanded, intellectual property has become a subject of front-rank legal importance. Cambridge intellectual property and information law is a series of monograph studies of major current issues in intellectual property. Each volume contains a mix of international, European, comparative, and national law, making this a highly significant series for practitioners, judges and academic researchers in many countries"--
Keywords: Intellectual property / European Union countries; Intellectual property (International law); Agreement on Trade-Related Aspects of Intellectual Property Rights / (1994 April 15); Kur, Annette; Agreement on Trade-Related Aspects of Intellectual Property Rights (1994 April 15); Intellectual property; European Union countries; Festschrift